Profile of immune response during nasal challenge with dermatophagoides pteronyssinus in subjects with allergic airway diseases - Laura Tamasauskiene; Brigita Gradauskiene (BMC, 2024)
Abstract Background T lymphocyte helper (Th) 2 plays the main role in pathogenesis of allergic airway diseases (AAD). Recent studies showed that interleukin (IL) 33, Th17 and Th22 also may be involved in allergic inflammation. The aim is to evaluate cytokine level before and after nasal challenge with Dermatophagoides pteronyssinus in patients with AAD. Methods Patients with persistent allergic rhinitis (AR) with or without allergic asthma (AA) allergic to house dust mite and healthy individuals underwent nasal challenge with Dermatophagoides pteronyssinus. Measurements of IL-13, IL-17, IL-22 and IL-33 in serum and nasal lavage were performed before, 2 and 22 h after nasal challenge by ELISA. Results . Ten patients with AR only, 6 patients with AR and AA and 7 healthy individuals were involved in the study. Serum IL-22 level significantly increased in patients with AR and AA and nasal lavage IL-22 tended to increase in patients with AAD after nasal challenge. Serum IL-13 level tended to increase in patients with AR and AA. IL-13 level in nasal lavage fluid decreased at 22 h after nasal challenge in patients with AR only. IL-17 level in serum and nasal lavage decreased in patients with AAD. Serum IL-33 tended to increase after nasal challenge whereas IL-33 in nasal lavage significantly decreased. Conclusion Cytokine profile differs between local and systemic compartments and between patients with allergic rhinitis only and patients with allergic rhinitis and asthma after nasal challenge.